Segurança e tolerabilidade de um enxaguatório bucal a base do óleo essencial das folhas de Cinnamomum zeylanicum Blume (Canela) com ação sobre a Candidose e seu efeito sobre propriedades físicas da resina acrílica - Oliveira, Julyana de Araújo (2014)
The Cinnamomum zeylanicum Blume leaf (Cinnamon) essential oil has been reported in the literature by presenting antifungal activity against Candida species. This study aimed to verify the in vitro antifungal activity of a Cinnamomum zeylanicum Blume leaf essential oil based mouthwash, in addition to changes in roughness and hardness caused by it in thermopolymerizable acrylic resin. Further evaluation of the safety and tolerability of the test product was seeked through a phase I clinical trial involving users of removable dentures. For this to happen, the determination of the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) on twelve strains of Candida, using the technique of Sabouraud Dextrose Broth microdilution (CSD) and subculture on Sabouraud Dextrose Agar (SDA), respectively. For microhardness tests and surface roughness, 30 specimens were made in thermopolymerizable acrylic resin (Vip Flash, Ltda. São Paulo, SP, Brazil), divided into three groups of n = 10. Group I remained in artificial saliva during the test, while groups II and III remained for 1 minute, 3 times a day, in their corresponding solutions (mouthwash and nystatin, respectively), returning to neutral artificial saliva during 15 days. Roughness measurements (SJ-201 Minutayo, Kawasaki, Japan) and microhardness (Shimadzu, Kyoto, Japan) were performed (24 hours before and 24 hours after the start and end of the test) to obtain data on the roughness and microhardness (25g / 30s), which were submitted to ANOVA and followed by Tukey post-test (α = 5%). For the phase I clinical trial, 15 healthy patients using a C. zeylanicum mouthwash in CIM (15 days, 3 times a day) were submitted to clinical and mycological examinations before and after the intervention. The essential oil of C. zeylanicum showed anti-Candida activity on the 12 strains tested, with an MIC = 625.0μg/mL equivalent to CFM. All groups experienced an increase in roughness after the intervention (p <0.0001). The test product group (GII) suffered alteration (ΔRa) of 0.40μm, not statistically different from the group that remained immersed in saliva (GI) whose value was ΔRa 0.39μm. Nystatin (GIII) showed the largest increase in roughness (ΔRa = 0.50μm) compared to GI and GII (p <0.0001). Regarding hardness, nystatin also promoted a greater decrease (ΔM = -3.62VHN) compared to saliva (ΔM = -2.57VHN) and mouthwash, which promoted change of -2.12VHN (p <0.0001). Regarding the clinical stage of phase 1, there were no adverse clinical signs after the intervention, or relevant reports indicating that suspension of use. The mouthwash showed antifungal activity against all tested strains and promoted minor variation of roughness and hardness of acrylic resin compared to positive control (nystatin). These factors combined with the absence of adverse effects in humans make it possible to consider, in this study, satisfactory safety and tolerability of the tested substance, supporting new advances involving the clinical use of C. zeylanicum Blume essential oil.